A significant episode. Viktor Tausk in Lublin and his research on war psychoses - DOMAŃSKI, CEZARY W. (Studia Psychologica: Theoria et praxis, 2016)
Viktor Tausk, an Austrian lawyer, a writer and a doctor, had ties to the psychoanalytic movement in the first decade of the 20th century. In fall of 1909 he became member of the Vienna Psychoanalytic Society. He participated in the Wednesday meetings with Sigmund Freud and other pioneers of psychoanalysis. He served as a physician- -psychiatrist in the Austro-Hungarian army. He was stationed in Lublin for a period of nine months. It was there that he gathered and analyzed the material, that formed the basis for his two important works: one of them concerned the so called ‘war psychosis’, the other the psychology of deserters.